Kritik terhadap Pendekatan Psikologi Meyer dalam Analisis Musik - Andre Indrawan (EKSPRESI, 2010)
Criticism toward Meyer’s Psychological Approach in Music Analysis. This paper discusses a psychological approach to music analysis introduced by Leonard Meyer that has been criticized by Nicolas Cook (1987). Meyer’s rhythmical and linear analysis which focused on the foreground expectation is less practical in observing large-scale musical structure. In terms of its benefit to advancing musical performance interpretation, the strength and weakness of the approach have been compared to the Shenkerian method which gives more attention to the harmonic reduction that focused on the harmonic background. Although the critic concentrates on technical analysis only, Meyer’s analysis would be valuable to the Shenkerian side if they also take into account his concept of musical style which is mostly regarded as the area of aesthetic rather than technical analysis.  Keywords: Critic, psychological of music, music analysis